Pre - Purchasing and Post - Purchasing Travel Behavior on Social Media: The Case of Kazakhstan - ABDUNUROVA, Assem; USPANOVA, Maira; HASAN, Rajibul; SURAPBERGENOVA, Zinagul; KUDAIBERGENOV, Nuradin (Journal of Environmental Management and Tourism; Vol 11 No 6 (2020): JEMT Volume XI, Issue 6(46) Fall 2020DO - 10.14505/jemt.11.6(46).18, 2020)
Purpose – To identify consumers’ travel behavior on social media (SM) before and after purchasing tourism product in the case of the Republic of Kazakhstan. Methodology – A quantitative survey collected data involving travel purposes from 413 users of SM platforms. Findings – This paper revealed the impact of social-economic characteristics on travel behavior and characterized two stages of purchasing process tourism product on SM: The pre-purchase behavior: the impact on decision-making process such factors as sources of trustworthy content, travel frequency, being a member of travel companies’ SM and feedback from travel companies; The post-purchase behavior: the impact of satisfaction and dissatisfaction on the level of spreading positive and negative reviews; feedback from travel companies on consumers’ satisfaction, frequency usage of SM. The originality – The paper investigated pre-purchasing and post-purchasing travel behavior on SM and lack of researches and online travel behavior statistics in Central Asia makes this paper valuable.